The Presentation of Gender Identity on Female Travel Blogs - Sidiq Hari Madya (BUANA GENDER : Jurnal Studi Gender dan Anak, 2018)
Blogs as a growing online platform came to be seen as a â€˜newly idealâ€™ space for social interaction, identity construction and negotiation. Bloggers became a social actor who showcase and perform their roles and identities online. This paper would attempt to analyse the presentation of gender identities on travel blogs managed and written by female travellers. The research questions raised were â€œhow online technology (travel blogs) become a space for women to perform gender identity online? In performing their identity, how these women may challenge the conception of male domination in â€œtravel worldâ€ as presented through their narratives in a travel blog?â€ Adopting West and Zimmermanâ€™s (1987) concept of doing gender, gender identities would be viewed as something individuals achieve or accomplish through ongoing social interactions (p. 129). The study found that travel blogs have become a space for female travellers to express and extend their identities online. Female identity presented in travel blogs substantially informs the traditionally exclusion of women in travel world. As has also been elaborated, travelling itself can be understood as a gendered phenomenon. Since traveling is gendered, perception of being on the road and the roles played by male and female traveller is different.